User Experience of a Bespoke Videoconferencing System for Web-Based Family Visitation for Patients in an Intensive Care Unit: 1-Year Cross-Sectional Survey of Nursing Staff - Aoife Murray; Irial Conroy; Frank Kirrane; Leonie Cullen; Hemendra Worlikar; Derek T O'Keeffe (JMIR Human Factors)
Abstract BackgroundDuring the COVID-19 pandemic, in-person visitation within hospitals was restricted and sometimes eliminated to reduce the risk of transmission of SARS-CoV-2. Many health care professionals created novel strategies that were deployed to maintain a patient-centered approach. Although pandemic-related restrictions have eased, these systems, including videoconferencing or web-based bedside visits, remain relevant for visitors who cannot be present due to other reasons (lack of access to transport, socioeconomic restraints, geographical distance, etc). ObjectiveThe aims of this study were (1) to report the experience of intensive care nursing staff using a bespoke videoconferencing system called ICU FamilyLink; (2) to examine the scenarios in which the nursing staff used the system; and (3) to assess the future use of videoconferencing systems to enhance communication with families. MethodsA modified Telehealth Usability questionnaire was administered to the nursing staff (N=22) of an intensive care unit in a model 4 tertiary hospital in Ireland 1 year after implementing the bespoke videoconferencing system. ResultsIn total, 22 nurses working in the intensive care department at University Hospital Galway, Ireland, responded to the survey. A total of 23% (n=5) of participants were between the ages of 25 and 34 years, 54% (n=12) were between 35 and 44 years, and 23% (n=5) were between 45 and 54 years. Most (n=15, 68%) of the participants reported never using videoconferencing in the intensive care setting to communicate with family members before March 2020. The modified Telehealth Usability Questionnaire showed overall satisfaction scores for each subcategory of ease of use and learnability, interface quality, interaction quality, reliability, satisfaction and future use, and usefulness. In total, 21 (95%) participants agreed or strongly agreed with the statement, “I would use the ICU FamilyLink system in future circumstances in which family members cannot be physically present (ie, pandemics, abroad, inability to travel, etc),” and 1 participant responded neutrally. One participant highlighted a common scenario in intensive care settings in which a videoconferencing system can be used “Even without COVID, web-based communication is important when patients become unexpectedly ill and when families are abroad.” ConclusionsThis study provides valuable insights into health care professionals’ experience using a videoconferencing system to facilitate web-based visits for families. We conclude that videoconferencing systems when appropriately tailored to the environment with the users in mind can be an acceptable solution to maintain communication with family members who cannot be physically present at the bedside. The bespoke videoconferencing system had an overall positive response from 22 nursing staff who interacted with the system at varying frequency levels.